2020
DOI: 10.1108/bpmj-05-2020-0207
|View full text |Cite
|
Sign up to set email alerts
|

A systematic literature review on the usage of eye-tracking in understanding process models

Abstract: PurposeBusiness process modeling can involve multiple stakeholders, so it is natural that problems may occur during the designing and understanding processes. One way to perceive these problems is to evaluate the comprehension of business process models through the collection of data related to the readers' eye movement via an eye-tracking device. The purpose of this paper is to provide a comprehensive overview of the use of eye-trackers in understanding process models and to offer a research roadmap to challe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 51 publications
0
8
0
1
Order By: Relevance
“…Past studies using eye-tracking in process models comprehension tasks found that visual attention and scan paths are influenced by the past work experience and personal knowledge (Petrusel et al, 2017;Zimoch et al, 2018b). However, these results are inconsistent as other research found that expertise had no immediate effect on model comprehension (Zimoch et al, 2018a;Batista Duarte et al, 2021). As the eye tracking literature is not mature enough in the field of process model comprehension, we have extended our literature review to include studies identifying the differences in visual attention between experts and novices in different types of search tasks.…”
Section: Visual Attentionmentioning
confidence: 98%
See 3 more Smart Citations
“…Past studies using eye-tracking in process models comprehension tasks found that visual attention and scan paths are influenced by the past work experience and personal knowledge (Petrusel et al, 2017;Zimoch et al, 2018b). However, these results are inconsistent as other research found that expertise had no immediate effect on model comprehension (Zimoch et al, 2018a;Batista Duarte et al, 2021). As the eye tracking literature is not mature enough in the field of process model comprehension, we have extended our literature review to include studies identifying the differences in visual attention between experts and novices in different types of search tasks.…”
Section: Visual Attentionmentioning
confidence: 98%
“…Recent studies have used the eye-tracking methodology to investigate the understanding of process models in 10.3389/fnins.2022.982764 different comprehension tasks (Batista Duarte et al, 2021). As comprehension of process models cannot be directly observed and measured; eyetracking studies use the visual attention measures paired with comprehension correctness to identify patterns linking the scan path or cognitive load to model understanding (Petrusel and Mendling, 2013;Batista Duarte et al, 2021).…”
Section: Visual Attentionmentioning
confidence: 99%
See 2 more Smart Citations
“…Adapun teknik Studi Literatur, peneliti lakukan dengan cara mencari bahan-bahan bacaan yang relevan dengan objek penelitian ini (Duarte et al, 2020). Bahan-bahan bacaan itu dapat berupa buku, artikel jurnal dalam bentuk tercetak yang dapat peneliti dapati di Perpustakaan UIN Sunan Gunung Djati Bandung.…”
Section: Metodeunclassified